Directory of industry and commerce : Jamaica (Jamaica National Investment Promotion Limited KingstonJM, 1985)
Contains lists of all Jamaican manufacturing and services companies; exporters of non-traditional agricultural and horticultural products; foreign firms, subsidiaries and affiliates operating in Jamaica and Jamaican missions overseas.
IDS